Variations in the association between education and self-reported health by race/ethnicity and structural racism - Riley Whiting; Suzanne Bartle-Haring (Elsevier, 2022)
Research has documented a longstanding association between education achievement and physical health outcomes. However, research has suggested that the health benefits gained from education differ by race, with minoritized racial groups generally experiencing poorer health and fewer health benefits from education. One potential explanation for this phenomena of "diminished returns" is the influence of structural racism. The purpose of this paper is to assess how structural factors at the state level are associated with self-reported health and the association between education and health. Utilizing a sample (N = 6819) from the NLSY dataset, measures of structural racism (political participation, employment and job status, education attainment and judicial treatment) were used to assess the hypotheses. Results indicated significant differences in key areas, with some nuanced findings - indicating that structural racism is an important health factor. These indicators of structural racism are discussed in the context of complexity of linked lives. Further research regarding structural racism, education, health and developmental stages is warranted.